Exosomal Non-coding RNAs-Mediated Crosstalk in the Tumor Microenvironment - Chen, Qi; Li, Yuefeng; Liu, Yueqin; Xu, Wenlin; Zhu, Xiaolan (Frontiers in Cell and Developmental Biology, 2021)
Exosomes are secreted by different types of cells in tumor microenvironment (TME) and participate in multiple biological processes of tumors. Non-coding RNAs (ncRNAs) enveloped in exosomes and released to the TME are shown to be involved in tumorigenesis and development, as well as act as important intracellular communicated mediators. However, the understanding on the exact regulatory functions and substrates of exosomal RNA are still at an early stage. In this review, we provided an overview on recent studies on exosomes mediating the modulation of both tumor cells and immune cells, then summarized the exosomal ncRNAs (such as miRNAs, lncRNAs and circRNAs) secreted by tumor cells and stromal cells that exhibited potential capabilities to regulate tumor cell growth, progression, metastasis, drug resistance, and immune response. Our review may hopefully inspire deeper understanding on the ncRNAs’ function as useful biomarkers for the diagnosis, prognosis, and as novel targets therapy for cancer.